PENGARUH TEKANAN ANGGARAN WAKTU DAN SIKAP SKEPTISME PROFESIONAL AUDITOR TERHADAP KEBERHASILAN DALAM MENDETEKSI KECURANGAN KLIEN PADA KANTOR AKUNTAN PUBLIK DI KOTA PALEMBANG - Apriyanto, Apriyanto (Universitas Muhammadiyah Palembang, 2016)
Audit quality assurance related to the auditor that the financial statements do not present any material errors or fraud load. Fraud must be investigated and sought the truth. Thus, an auditor should apply professional skepticism attitude. An auditor in doing their jobs must be professional and competitive in order to give satisfaction to the clients. Auditors are often in a dilemma situation.Data analysis methods to be used by the author in this study is the analysis of quantitative and qualitative analysis. The data used in this study are primary data and secondary data. The results showed budget pressure and attitude of professional skepticism, the auditor together positive and significant impact on the success in detecting fraud clients. Partial budget pressure has a negative relationship and the direction of the client's success in detecting fraud and attitude of professional skepticism partially auditor has a positive relationship and the direction of the client's success in detecting fraud.